REPRESENTASI BUDAYA PATRIARKI DALAM FILM "KIM JI-YOUNG, BORN 1982":Kajian Semiotika John Fiske - Alfiansyah Ramdhani (2020)
Patriarchal culture places women in lower position than men. This culture give rise to discrimination and violence against women who break human rights. Film being a tool that can be used to educate the public about the issue of patriacrchal culture because film is a mass media with capable to reach everyone. The film "Kim Ji-Young, Born 1982" is one of the films that show the dangers of patriarchal culture. John Fiske's semiotic theory can be used to discuss symbols representing patriarchal culture in the film "Kim Ji-Young, Born 1982" because John Fiske theory interprets symbol in the media to display the ideology and culture. Keywords: Representation, Semiotic, Film, Patriarchy, Women